2023
DOI: 10.1108/bpmj-10-2022-0546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of data analytics-oriented business intelligence technology effectiveness: an enterprise-level analysis

Abstract: PurposeA crucial question still remains unanswered as to whether data analytics-oriented business intelligence (hereafter, BI) technologies can bring organizational value and benefits. Thereby, several researchers called for further empirical research to extend the limited knowledge in this critical area. In an attempt to deal with this issue, we presented and tested a theoretical model to assess BI effectiveness at the organizational benefits level in this research article.Design/methodology/approachThe sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…In a similar vein, Kefi and Koppel (2011) in their empirical study found that user satisfaction and individual performance are positively influenced by a high quality of the BIS. In addition, a number of studies confirmed that system quality has a positive impact on user satisfaction and performance (Al-Okaily et al, 2023;Al-Soni and Abu-Shanab, 2021;Al-Okaily et al, 2022a). Based on these discussions, we hypothesize the following: H1.…”
Section: System Qualitymentioning
confidence: 78%
See 1 more Smart Citation
“…In a similar vein, Kefi and Koppel (2011) in their empirical study found that user satisfaction and individual performance are positively influenced by a high quality of the BIS. In addition, a number of studies confirmed that system quality has a positive impact on user satisfaction and performance (Al-Okaily et al, 2023;Al-Soni and Abu-Shanab, 2021;Al-Okaily et al, 2022a). Based on these discussions, we hypothesize the following: H1.…”
Section: System Qualitymentioning
confidence: 78%
“…Overall, the above research confirms the validation and reliability of the DeLone and McLean model to measure the BIS efficiency from the user benefits viewpoint, not the organizational benefits. This gap has been recognized in calls for using the DeLone and McLean model to measure BIS efficiency in the organizational context (Al-Okaily et al ., 2023; Gonzales and Wareham, 2019; Gaardboe et al , 2017). Meanwhile, a review of the literature indicates that the majority of the empirical studies in this research field have been undertaken in developed counties with a few from less developed and developing countries such as Jordan.…”
Section: Literature and Theoretical Foundationsmentioning
confidence: 99%
“…, 2022a, b), which turned the traditional business form toward smart business (Al-Khatib and Ramayah, 2023; Chatterjee et al. , 2022; Al-Okaily et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of the fourth industrial revolution concept, which constituted the turning point in adopting emerging technologies related to Industry 4.0, firms became more able to define their requirements and elements of their organizational success (Al-Khatib and Ramayah, 2023). These firms became smarter than before due to using big data analytics (BDA) and artificial intelligence (AI) techniques (Tortorella et al, 2022a, b), which turned the traditional business form toward smart business (Al-Khatib and Ramayah, 2023;Chatterjee et al, 2022;Al-Okaily et al, 2023).…”
mentioning
confidence: 99%
“…BI facilitate non-expert computer users to analyse and visualise linked data, thus generating actionable information by means of reporting, OLAP analysis, dashboards or data mining (Corrales-Garay et al ., 2022). Thanks to this information, organizations can track their performance comparing indicators with business objectives and competitors, analyse consumer behaviour, discover problems and predict success, which allows them to make better decisions to improve processes and results (Al-Okaily et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%